Learning from domestic homicide reviews in England and Wales. (7th November 2019) - Chantler, Khatidja; Robbins, Rachel; Baker, Victoria; Stanley, Nicky
Abstract: This paper aims to contribute to the prevention of future domestic homicide by analysing 141 domestic homicide reviews (DHRs) in England and Wales. All publicly available DHRs ( n = 141) were retrieved from Community Safety Partnership websites in England and Wales in June 2016. Utilising a mixed methods approach, we designed templates to extract quantitative and qualitative data from DHRs. Descriptive statistics were generated by SPSS. 54 DHRs were analysed qualitatively, using N‐Vivo for data management. The findings revealed that perpetrators were aged: 16–82 years; with a mean average age of 41 years. Victims' ages ranged from 17 to 91 years old; with a mean average age: 45 years. Perpetrators' mental health was mentioned in 65% of DHRs; 49% of perpetrators had a mental health diagnosis. Healthcare services, in particular, mental health services, were most likely to be involved with perpetrators. 'Movement' was identified as a key contextual feature of the 54 DHRs analysed qualitatively and this was found to interact with risk assessment, language barriers and housing problems. In conclusion, domestic violence and abuse risk assessments need to be informed by the knowledge that domestic abuse occurs across the age span. Mental health settings offer an opportunity for intervention to prevent domestic homicide. Domestic Homicide Reviews can provide valuable material for training practitioners.